Effect of the modified Heisenberg algebra on the black hole thermodynamics. (30th March 2021) - Hamil, B.; Lütfüoğlu, B. C.
Abstract: In this letter, we introduce two new forms of uncertainty relations by extending the usual Heisenberg algebra with higher terms. Within these scenarios, at first, we study the Unruh temperature. We find that the Unruh temperature increases in one of the new forms while it decreases in the other form. Next, we explore the thermodynamic properties of a Schwarzschild black hole by relying on these two new forms of the Heisenberg uncertainty relation. We present the modifications in the mass-temperature, specific heat, and entropy functions of the black hole according to the extension parameters.